MENDORONG PERTUMBUHAN EKONOMI MELALUI PENINGKATAN PARTISIPASI SOSIAL: Studi Kasus Pembangunan Ekowisata di Desa Mandak - Akhmad Munif Mubarok; Lukman Wijaya Barata; Siti Sundari (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2020)
This article explores public awareness in shaping ecotourism in Mandak Village. Participation through the development of Watu Rumpuk Tourism in Mendak Village, Perdagangan District, Madiun Regency is one of the uses of social participation in an effort to encourage the economic growth of the Mendak Village community. This research approach is qualitative and type of research uses descriptive studies. Determination of informants in research using purposive techniques. Data collection techniques are observation, interviews, and documentation. Data analysis uses data reduction, data presentation, and drawing conclusions and verification. The data validity technique uses source triangulation. The results showed that participation formed by the Mendak Village community was a form of horizontal participation. Where horizontal participation is participation born from community self-awareness in dealing with existing problems. The background of the formation of this participation comes from the condition of clove harvest failure which is a common problem. Then the problem solving is obtained by exploiting natural potential, namely tourism development. Development activities are carried out in mutual cooperation until there is economic growth, all these activities are a form of development carried out by community participation. The participation in Watu Rusun tourism development can occur because of the willingness of the community to be involved in tourism development, the opportunities provided by the community, and the ability of the community to utilize tourism. The benefits of participation in tourism development for the community are the availability of new jobs, the emergence of businesses in processing local potential, and the existence of CSR from investors for tourism development.Keywords: Failure of Clove Agriculture, Social Participation, Watu Rusun Tourism Development, community economic growth.